Efecto de la temperatura en el valor de Monocapa de tres tipos de Harina de Tarwi (lupinus mutabilis) variedad criolla mediante la isoterma de gab - Briceño Sevillano, Santos Martin (2017)
The objective of the present work was to evaluate the effect of temperature on the monolayer value of three types of flour of Andean lupin (Lupinus mutabilis) creole variety using the GAB model. Also, the effect of the temperature on the isosteric heat value (kJ/kg). For the construction of the isotherms, solutions of sulfuric acid were used as controlling agent of water activity. The water activities were worked up from 0,1 to 0,9. The types of flour were dull (type A), dull and defatted (type B) and dull, defatted and proteolyzed (Type C). The influence of temperature on the monolayer value was determined by the LSD test, finding a significant difference for the three temperatures (20, 30 and 40 ° C) in all three types of flour. The GAB monolayer value decreases with increasing temperature, ranging from 0,0648 g/g to 0,0397 g/g for type A flour; From 0,0915 g/g to 0,0567 g/g for type B flour and from 0,0208 g/g to 0,0130 g/g for type C flour. Similarly, the isosteric heat decreases with increasing temperature. The analysis of variance shows a significant difference in the effect of temperature. The defatted flour showed a higher monolayer value for the same temperature. Conversely, type C flour had the lowest values of monolayer.